Effect of organic liquid process control agents on properties of ball-milled powders - Gandhi, Purvam Mehulkumar; Valluri, Siva Kumar; Schoenitz, Mirko; Dreizin, Edward L. (Advanced powder technology)
Despite widespread use of liquid process control agents (PCA) during material processing via high-energy ball milling, their effect on the properties of the milled powders has not been quantified or understood. It is generally accepted that PCA affect the energy transfer between milling tools and powders being milled; however, which PCA properties are particularly important is not known. It is further unclear how to select a proper PCA depending on the specific objectives set for preparation of the milled materials. Here, an approach is offered to begin developing respective selection criteria and determine the correlations between different PCA properties and milling outcomes. Two powders, Bi2O3 and CuO, are milled using the same conditions and only varying liquid PCA. A set of thirteen organic liquids served as variable PCAs. Correlations between particle and crystallite sizes of the milled powders and multiple PCA properties were identified. PCA density affected both particle and crystallite sizes for both oxides. However, the effect of density was less significant when compared to those of other parameters uniquely important for specific milling outcomes for specific oxides. The significant correlations of particle sizes for Bi2O3 and CuO were with PCA proton affinity and surface tension, respectively. Crystallite sizes of Bi2O3 and CuO correlated respectively most strongly with the PCA dynamic viscosity and density. It is proposed that both physical and chemical interactions between PCA and powder affect the milling outcomes. Chemical interactions are specific for each powder/PCA pair and contribute most directly to changing particle and crystallite sizes of the powder being milled. Physical interactions are more generic. The approach developed here is found to be useful and, with a significantly expanded database, is expected to help developing a practical guide for selecting the PCA depending on the powder characteristics and the desired outcome of the material processing by milling. (c) 2021 The Society of Powder Technology Japan. Published by Elsevier BV and The Society of Powder Technology Japan. All rights reserved.